A preliminary combined simulation tool for the risk assessment of pedestrians' flood-induced evacuation. (October 2017) - Bernardini, Gabriele; Postacchini, Matteo; Quagliarini, Enrico; Brocchini, Maurizio; Cianca, Caterina; D'Orazio, Marco
Abstract: Flood risk assessment in urban regions does not account for human behaviours during emergency. Understanding behaviours during floods and developing related simulators highlight critical phenomena for individuals' safety, during and after the flood, and suggest risk-reduction strategies aimed at helping evacuees. The proposed Flooding Pedestrians' Evacuation Dynamics Simulator (FlooPEDS) combines flood hydrodynamics (based on Nonlinear Shallow Water Equations) and individuals' evacuation (by modifying the Social Force Model). FlooPEDS capabilities are illustrated with reference to an important case study. Results focus on evacuees' motion and path choices. This preliminary simulator implementation, still raw for practical use by planners and authorities, is already mature to guide the design of innovative resilience-increasing urban solutions (i.e.: architectural components like handrails, raised flooring systems) in specific hazardous urban areas, as support to traditional strategies (i.e.: early warning systems; evacuation plan communication). Highlights: We develop a combined model for the evacuation of pedestrians in a urban flood. Hydrodynamic modelling of the flood based on a shallow-water type solver. Human evacuation adopts a experimental-based modified Social Force Model. We perform model setup activities and apply it to a case study. Model application can outline risk reduction strategies based on evacuees' threats.